Microscopia eletrônica de varredura de duas espécies de Fannia Robineau-Desvoidy (Diptera, Fanniidae) - Al Gazi, Ariel David Freitas [UNESP]; Bélo, Muracy [UNESP]; Santos, Jaime Maia dos [UNESP] (Sociedade Brasileira de Entomologia, 2004)
As espécies Fannia pusio Wiedeman, 1830 e Fannia trimaculata Stein, 1898 pertencem ao grupo canicularis e ao subgrupo pusio. Estas espécies são morfologicamente muito similares e geralmente são diferenciadas por uma fileira de cerdas no fêmur do terceiro par de pernas do macho. A análise com microscopia eletrônica de varredura mostrou na estrutura denominada cellas, menor número de orifícios na superfície dorsal do ovo e, na superfície ventral, foi detectado menor rugosidade, ambos em F. trimaculata. Na larva, o estigma ou espiráculo protorácico é proeminente, onde F. trimaculata apresentou duas expansões tegumentares pequenas e sete longas de igual comprimento. Os machos de F. trimaculata apresentam uma fileira de cerdas localizadas mais externamente na faceta e, outra fileira de cerdas menores, a qual é ausente em machos de F. pusio, porém presente nas fêmeas de ambas as espécies.

Scanning electron microscopy in two species of Fannia Robineau-Desvoidy, (Diptera, Fanniidae). The species Fannia pusio Wiedemann, 1830 and F. trimaculata Stein, 1898 belong to the canicularis group and pusio subgroup. These species are morphologically very similar and usually distinguished from each other by a line of bristles on the males hind femur. The scanning electron microscopy analysis showed a smaller number of orifices on the dorsal surface of the egg in the structure called cellas and, on the ventral surface, less rugosity was noted, both in F. trimaculata. on the larvae, the stigma or protothoracic spiracle was outstanding, where F. trimaculata possess two short tegumental extensions and seven long ones, while F. pusio has nine extensions, all long, of equal length. Males of F. trimaculata present alongside a line of longer bristles located more externally on the facet, another line of shorter bristles, which is absent in males of F. pusio, but present in females of both species.
Keywords: Differences; Fannia pusio; Fannia trimaculata; Morphology; SEM; Fannia pusio; Fannia trimaculata; Morfologia; SEM